Directional X-ray response of mercuric bromide films - Sasen, Natalia; Pérez, Maria Eugenia; Fornaro, Laura (Scientia Plena, 2011)
HgBr2 was synthesized from HgO, HNO3 and NaBr in aqueous solution. The material was then purified by two sublimations at 220 oC and with an initial pressure of 4 x 10-3 Pa. HgBr2 films were grown by the Physical Vapor Deposition (PVD) method onto 1h x 1h glass substrates. Growth conditions were a source temperature of 120-220 oC and a growth temperature of 50-140 oC; growth time was between 2 and 16 hours at an initial pressure of 4 x 10-3 Pa. The thickness of the films was between 100 and 1500 ƒÊm. For studying the anisotropic X-ray response of the films, growth conditions of no-adhesion between film and substrate were used: a source temperature of 190 oC, a growth temperature of 80 oC and a growth time of 2 hours. Films of 1500 ƒÊm in thickness were obtained, and were characterized by SEM and AFM. Detectors were then constructed in order to check the response of the films along and perpendicular to the substrate plane, by palladium thermal deposition, palladium wire attachment with aquadag and acrilic encapsulation. Whatever the considered direction, the electrodes were ohmic. Resistivities in the order of 1011 ƒ¶.cm for both directions were obtained when dark current was measured perpendicular or parallel to the substrate. When irradiated with 241Am source, films gave the same signal to noise relations of 1.5 at 50 V for both, perpendicular and parallel conduction respectively. Detectors are not sensitive to light, therefore they do not need light shielding when used as X-ray sensors. Resistivity and X-ray response results show similar values for both, perpendicular and parallel conduction. This result does not agree with the expected anisotropy that may be attributed to a layer compound. However, the lack of orientation of the film microcrystals, confirmed by SEM images, may be responsible for this result.